the Development of Assessment Instruments Non-Cognitive by Teachers - Aloysius Mering; Indri Astuti (STKIP Singkawang, 2019)
This study aims to (1) describe clearly and comprehensively about the quality of non-cognitive assessment instruments made by elementary school teachers, (2) develop procedures for developing non-cognitive assessment instruments made by teachers, (3) develop non-cognitive assessment instruments made by teachers. To realize this goal, researchers used three structured research designs. The first design is survey research to describe the quality of non-cognitive assessment instruments made by teachers. The instruments studied are survey data, which are illuminated by non-cognitive instruments constructed by the teacher in the Lesson Plan (RPP). Furthermore, from the results of a review of the teacher's non-cognitive assessment instruments, a guidebook on the procedure for developing cognitive assessment instruments made by teachers will be developed. The development of the guidebook uses development procedures (R & D). In the third draft, the researcher and the teacher developed a non-cognitive assessment instrument in the workshop. This workshop is the application of the guidebook that has been prepared. The procedure for preparing instruments uses steps (a) development of instrument specifications, (b) instrument writing, (c) instrument review, (d) instrument assembly (for testing purposes), (e) instrument testing, (f) results analysis trial, (g) instrument selection and assembly, (h) printing instruments, (i) administration of instruments, and (j) preparation of scales and norms. The whole series of studies will produce outputs (a) research reports, financial reports, and logbooks, (b) articles that have been discussed, (c) guidelines for preparing non-cognitive assessment instruments made by teachers that can be used as teaching materials and alternative materials for drafting training assessment instruments, (d) scientific publications in accredited journals, (e) a collection of validated non-cognitive assessment instruments made by teachers.